Design of an Ultra-Wideband Transition from Double-Sided Parallel Stripline to Coplanar Waveguide - Young-Gon Kim; Kang Wook Kim (International Journal of Antennas and Propagation)
A design method of an ultra-wideband transition from double-sided parallel stripline (DSPSL) to coplanar waveguide (CPW) is proposed based on analytical expressions of characteristic impedance. The conformal mapping is used to obtain the characteristic impedance for each section of the transition within 3.7% accuracy as compared with the EM simulation results. An efficient and clear guideline for the design of the transition is proposed. The implemented transition performs less than 0.6 dB insertion loss per transition for frequencies from 40 MHz to 12 GHz and less than 1.2 dB insertion loss to 27 GHz, which well exceeds the previous results in the literature.